An examination of cultural-economic model and public relations in the Malaysian Islamic banking system - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin Bin (2014)
By adopting the study of cultural-economic model of Gaither and Kandari (2014), the current study was designed to analyse the cultural-economic model of public relations practice of two prominent Islamic banks (full-fledged Islamic bank and Islamic window bank ) in Malaysia by focusing on their communication tool particularly websites. The study is advancing the understanding of Islam and public relation in the context of Islamic banks in Malaysia, an understudied area in public relation literature and enlightens the relationship between religion and public relations. The analysis identified six Islamic value orientations elements especially respect for religious authority, affinity with the past, fatalism, communal kinship, attachment to the eternal life and spirituality and idealism relative to public relation practice among the Islamic banks. The study concludes with observation that there is inseparable relationship between religion and culture in the context of Islamic banking industry in Malaysia.